Implementation of Innovative Learning with Child-Friendly School Concept in TK Students - Dede Rohayati; Wasliman Wasliman; Hendi Suhendrayana Muchtar; Waska Warta (UIN Sunan Gunung Djati Bandung, 2021)
This article research is based namely the low implementation of innovative learning with the concept of a child-friendly school. Considering that innovative learning is an integral part of implementing the concept of child-friendly schools which is the responsibility of school principals, teachers and education implementers.The school treats a good attitude towards students by educating children sincerely and with love like their own children; the learning method used is adapted to the needs of kindergarten children, the teaching and learning process is fun; involvement of students in learning, interesting and fun classroom arrangements, as well as a clean, beautiful, safe and orderly school environment, The concept of a child-friendly school, students are more confident in themselves, high intrinsic motivation, students are able and dare to make their own choices, students are responsible responsibility to accept the consequences that accompany their choice, students can adjust to their environment, students are not dependent on others.